Inflammatory and microbiological associations with near-fatal asthma requiring extracorporeal membrane oxygenation. Issue 1 (27th January 2020) - Patel, Sunil; Shah, Neeraj M.; Malhotra, Akanksha M.; Lockie, Christopher; Camporota, Luigi; Barrett, Nicholas; Kent, Brian D.; Jackson, David J.
Extracorporeal membrane oxygenation (ECMO) has developed as a critical tool permitting lung protection in severe respiratory failure. Its use was largely confined to acute respiratory distress syndrome [1]; however, as technology has advanced, it is now used in a range of respiratory diseases, including asthma. In the context of near-fatal asthma exacerbations, ECMO provides a management strategy for difficult-to-ventilate patients who would otherwise be unlikely to survive. Importantly, in asthma, traditional mechanical ventilation strategies can be associated with volutrauma and barotrauma due to the high pressures required in the presence of severe bronchospasm [2]. To date, there is a paucity of data for ECMO use in acute asthma and it is unknown whether specific clinical or inflammatory characteristics are associated with the need for ECMO. Patients with near-fatal asthma requiring ECMO are more likely to be younger and female and are also likely to have positive viral and fungal isolates on bronchoalveolar lavage when compared to those receiving conventional mechanical ventilation http://bit.ly/2S38SaC